The N-Terminal Domain of Bfa1 Coordinates Mitotic Exit Independent of GAP Activity in Saccharomyces cerevisiae - Yan Li; Kiwon Song (Cells, 2022)
The spindle position checkpoint (SPOC) of budding yeast delays mitotic exit in response to misaligned spindles to ensure cell survival and the maintenance of genomic stability. The GTPase-activating protein (GAP) complex Bfa1–Bub2, a key SPOC component, inhibits the GTPase Tem1 to induce mitotic arrest in response to DNA and spindle damage, as well as spindle misorientation. However, previous results strongly suggest that Bfa1 exerts a GAP-independent function in blocking mitotic exit in response to misaligned spindles. Thus, the molecular mechanism by which Bfa1 controls mitotic exit in response to misaligned spindles remains unclear. Here, we observed that overexpression of the N-terminal domain of Bfa1 (Bfa1-D16), which lacks GAP activity and cannot localize to the spindle pole body (SPB), induced cell cycle arrest along with hyper-elongation of astral microtubules (aMTs) as Bfa1 overexpression in Δbub2. We found that Δbub2 cells overexpressing Bfa1 or Bfa1-D16 inhibited activation of Mob1, which is responsible for mitotic exit. In anaphase-arrested cells, Bfa1-D16 overexpression inhibited Tem1 binding to the SPB as well as Bfa1 overexpression. Additionally, endogenous levels of Bfa1-D16 showed minor SPOC activity that was not regulated by Kin4. These results suggested that Bfa1-D16 may block mitotic exit through inhibiting Tem1 activity outside of SPBs. Alternatively, Bfa1-D16 dispersed out of SPBs may block Tem1 binding to SPBs by physically interacting with Tem1 as previously reported. Moreover, we observed hyper-elongated aMTs in tem1-3, cdc15-2, and dbf2-2 mutants that induce anaphase arrest and cannot undergo mitotic exit at restrictive temperatures, suggesting that aMT dynamics are closely related to the regulation of mitotic exit. Altogether, these observations suggest that Bfa1 can control the SPOC independent of its GAP activity and SPB localization.